An assessment of food habits and altitudinal distribution of the Asiatic black bear (Ursus thibetanus) in the Western Himalayas, Pakistan. Issue 11 (27th March 2017) - Ali, Ashfaq; Zhou, Zhixiang; Waseem, Muhammad; Khan, Muhammad Fiaz; Ali, Ishtiaq; Asad, Muhammad; Qashqaei, Ali Turk
ABSTRACT: The Asiatic black bear Ursus thibetanus is one of the least well-known species of mammals, and there have been few studies conducted to investigate its status and feeding behaviour, particularly in the north-western parts of Pakistan. We investigated the food habits and altitudinal distribution of the Asiatic black bear in the Kaghan Valley region of the western Himalayas, Pakistan. We interviewed local villagers (n = 180) about food items consumed by black bears, and collected signs (n = 178) of the presence of black bears at different altitudes. The villagers reported that the black bears predominantly inhabit the forests of Malkandi, Kamalban and Jaraid, and visit agricultural fields located at the edge of the forests. Oak ( Quercus spp.), guch ( Viburnum cotinifolium ), mulberry ( Morus spp.), fig ( Ficus palmata ), pomegranate ( Punica granatum ) and maize ( Zea mays ) were confirmed by 160 ( 89%) interviewees as food items consumed by black bears in the Kaghan Valley. We recovered the remains of 21 types of food items from 53 black bear scats. Dietary analysis showed that maize (22.64%), white mulberry ( Morus alba, 16.98%) and maple ( Acer spp., 11.32%) were the most frequently identified food items in black bear scats. We recorded shifts in food item selection from month to month. The total volume of crop remains found in scats was 31.38%, which was greater than that of other major food groups.This high volume of agricultural crops in the Asiatic bear diet is a source of continuing human–bear conflict in the region, and is a factor that needs to be taken into consideration when formulating management strategies to protect this International Union for Conservation of Nature (IUCN) Red list species.